(3GdETQGa Ydi eYQaI GdCWQGas - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s ((3eOQSI GdOh dYjI HOeTb s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdEeGe bGd bGd hGdOi (B: (3GdMeO ddg GdgGOi Edi GdQTGO CeG HYO aEf Gddg GNJai CeI eMeO Udi Gddg Ydjg hSde HYde GdESfGO s
(3BNQgG (B:s
(3bhdg (B: (3MOjK HYK QShd Gddg Udi Gddg Ydjg hSde SQjI BNQ GdLRA GdKGdK YTQ ef GdCUd hgh JeGe GdeLdO GdChd jJdhg Ef TGA Gddg ai GdeLdO GdKGfi MQa GdTjf Je GdeLdO GdChd s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdMOjK h GdeUWdMs